Innovation for the Development of Police Station Management in Thailand - Jaruprat, Koravic; Saengnoree , Amnuay; Teerawatananond, Thapong (Journal of Roi Kaensarn Academi, 2023)
Innovation is the process of generating ideas, developing solutions, or managing various problems that arise. Police stations are organizations that require the integration of innovation to improve service delivery and operational efficiency. The importance of applying innovation in police stations lies in their duties and the high number of people utilizing their services. This article aims to explore the meaning of innovation, the necessary forms of innovation for police management, types of innovation, technological innovations, projects related to police station innovation, factors influencing the adoption of innovation in organizations, and the establishment of an innovative culture for management implementation. This information serves as a reference for agencies or individuals interested in studying and applying innovation to enhance their knowledge in organizational innovation.